2012
DOI: 10.1007/s00374-011-0653-2
|View full text |Cite
|
Sign up to set email alerts
|

Plant-borne flavonoids released into the rhizosphere: impact on soil bio-activities related to plant nutrition. A review

Abstract: Plants produce and release in the surrounding soil, the so-called rhizosphere, a vast variety of secondary metabolites. Among them, flavonoids are the most studied, mainly for their role in the establishment of rhizobiumlegume symbiosis; on the other hand, some studies highlight that they are also important in the plant strategies to acquire nutrients from the soil, for example, by acting on its chemistry. The scope of this review is to give a quick overview on the types and amounts of plant-released flavonoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
130
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(153 citation statements)
references
References 253 publications
(299 reference statements)
4
130
0
3
Order By: Relevance
“…Ben-Moshe et al (2013) observed that CuO and Fe 3 O 4 ENMs did not change the total organic content or macroscopic properties of two types of soil but altered the humic substances in the soils. The authors also observed an effect on the soil microbial community, which has been reported in other studies (e.g., (Ben-Moshe et al, 2013;Cesco et al, 2012;Ge et al, 2011;Collins et al, 2012), but did not attempt to link changes in important soil properties with these effects. VandeVoort et al (2014) found that silver ENMs could limit denitrification processes in soil, but that the effects were dependent on ENM concentration and coating.…”
Section: Introductionsupporting
confidence: 67%
“…Ben-Moshe et al (2013) observed that CuO and Fe 3 O 4 ENMs did not change the total organic content or macroscopic properties of two types of soil but altered the humic substances in the soils. The authors also observed an effect on the soil microbial community, which has been reported in other studies (e.g., (Ben-Moshe et al, 2013;Cesco et al, 2012;Ge et al, 2011;Collins et al, 2012), but did not attempt to link changes in important soil properties with these effects. VandeVoort et al (2014) found that silver ENMs could limit denitrification processes in soil, but that the effects were dependent on ENM concentration and coating.…”
Section: Introductionsupporting
confidence: 67%
“…Among the organic molecules detected in the rhizosphere in addition to MS s , oxalate needs to be mentioned as for its abundance among rhizodepositions and for its direct involvement in the biological and efficient weathering of minerals (Jones and Wilson 1985;Adamo et al 1997). Flavonoids released by roots have a direct effect on soil minerals and on biological activity in the soil that play an important role in Fe solubilization processes (El Hajji et al 2006;Tomasi et al 2008;Cesco et al 2012). However, although the impact of flavonoids on soil microorganisms could also be of relevance in terms of microbe-mediated Fe oxidation-reduction in soil (Tomasi et al 2008;Cesco et al 2010Cesco et al , 2012, the relative contribution of these molecules to the Fe availability in the rhizosphere and to the use of this Fe source for plant nutrient acquisition has not yet been comprehensively studied.…”
Section: Fe Complexation Processesmentioning
confidence: 99%
“…Flavonoids released by roots have a direct effect on soil minerals and on biological activity in the soil that play an important role in Fe solubilization processes (El Hajji et al 2006;Tomasi et al 2008;Cesco et al 2012). However, although the impact of flavonoids on soil microorganisms could also be of relevance in terms of microbe-mediated Fe oxidation-reduction in soil (Tomasi et al 2008;Cesco et al 2010Cesco et al , 2012, the relative contribution of these molecules to the Fe availability in the rhizosphere and to the use of this Fe source for plant nutrient acquisition has not yet been comprehensively studied. It appears evident that the release of Fe III -complexing organic compounds by roots and microorganisms can contribute to Fe (hydr)oxides dissolution and/or to Fe mobilization from unavailable sources (see Figs.…”
Section: Fe Complexation Processesmentioning
confidence: 99%
“…Moreover, extraction was increased at higher temperature but not at higher pressure. Due to differences in soils and extraction methods it is not feasible to compare reported flavonoid concentrations and fate; as summarized in a review, contradictory results have been obtained (Cesco et al 2012). …”
Section: Fate Of Flavonoids In the Rhizospherementioning
confidence: 99%
“…This review focuses on flavonoids in rhizospheres, which are small regions around the roots of plants (Hartmann et al 2008), where flavonoids play important roles in biological communications. Because there have been several recent reviews on flavonoids in rhizospheres (Cesco et al 2012;Cheynier et al 2013;Hassan and Mathesius 2012;Weston and Mathesius 2013), this review does not include all relevant studies, but concentrates on the potential of flavonoids to act as plant-mediated signaling compounds for sustainable agriculture.…”
Section: Introductionmentioning
confidence: 99%